Production method of tantalum powder and tantalum powder obtained by method
By using metal magnesium in a hydrogen-containing atmosphere to reduce oxygenation activation and sintering the tantalum powder, the problems of complex processes, long cycles and low yields in the prior art are solved, and the high yield, low cost and high voltage resistance of the tantalum powder are achieved, meeting the requirements of high-reliability capacitors.
Patent Information
- Application Number
- CN202480002575.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-03-28
AI Technical Summary
In the prior art, when preparing capacitor-grade tantalum powder, the process is complex, the cycle is long and the yield is low, resulting in high production costs, and it is difficult to improve the voltage resistance and specific capacity of tantalum powder at the same time.
In a hydrogen-containing atmosphere, a tantalum powder is subjected to oxygen-lowering activation treatment in the molten salt, and the tantalum powder is sintered in the molten salt, and the excess metal magnesium is separated, thereby improving the yield and pressure resistance of the tantalum powder.
It achieves high yield and low production cost of tantalum powder, while improving the voltage resistance and specific capacitance of tantalum powder, meeting the requirements of high-reliable capacitors.
Smart Images

Figure CN119730980A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of smelting rare metal functional materials, and in particular relates to tantalum powder for making high-reliability capacitors and a manufacturing method thereof. Background Art
[0002] Tantalum electrolytic capacitors (hereinafter referred to as tantalum capacitors) have the advantages of high capacity, small size, strong self-healing ability and high reliability. They are widely used in high-end technical fields such as communications, computers, automotive electronics, medical equipment, radar, aerospace, and automatic control devices. Tantalum powder is the key material for making tantalum capacitors. Only by using tantalum powder for capacitors with excellent voltage resistance can tantalum capacitors with good reliability be produced, and the high reliability requirements of electronic devices and electronic circuits can be continuously met.
[0003] At present, the main methods for industrial preparation of capacitor-grade tantalum powder are sodium reduction potassium fluorotantalate method, magnesium reduction tantalum oxide method, tantalum ingot hydrogenation method, etc. No matter which method is used to prepare tantalum powder, in order to improve the electrical properties of tantalum powder, the prepared tantalum original powder needs to be subjected to high-temperature high-vacuum heat treatment, metal magnesium reduction and oxygen reduction and other subsequent treatments. Among them, the high-temperature high-vacuum heat treatment process can remove gas impurities and some low-melting point metal impurities, and metal magnesium reduction can reduce the oxygen content of tantalum powder and improve the distribution of oxygen in tantalum powder; and the subsequent treatment can also make the tantalum metal particles condense and sinter, thereby improving the tantalum metal particle structure and improving the electrical properties of tantalum powder. In order to improve the pressure resistance of tantalum powder, the general practice is to increase the sintering temperature, extend the sintering time and other measures, but increasing the sintering temperature and extending the sintering time will cause the loss of specific capacitance.
[0004] CN114210973B invented a sintering method that can improve the pressure resistance of tantalum powder while maintaining a high specific volume. Its characteristics are that after using metal magnesium to deoxidize and activate the tantalum powder in molten salt, the excess metal magnesium is separated, and the tantalum powder is sintered in the molten salt. After further water pickling and separation of the tantalum powder, high-temperature high-vacuum heat treatment, metal magnesium reduction and deoxidation, and pickling are performed to obtain tantalum powder with improved high-voltage electrical performance. However, the problem with this molten salt-assisted heat treatment method is that the yield is low and the process is relatively complicated.
[0005] However, the above-mentioned molten salt-assisted heat treatment method for preparing tantalum powder has problems such as a relatively complicated production process, a relatively long process cycle, a relatively low yield, and a high production cost. Summary of the invention
[0006] The purpose of the present invention is to provide a tantalum powder for capacitors with high breakdown voltage and capable of meeting the requirements for manufacturing high-reliability capacitors. Another purpose is to provide a method for preparing tantalum powder that can improve the yield of tantalum powder. The method is characterized in that the tantalum powder is subjected to oxygen reduction and activation treatment in a molten salt using metallic magnesium in a hydrogen-containing atmosphere, while the tantalum powder is sintered in the molten salt, and then excess metallic magnesium is separated.
[0007] The object of the present invention is to provide a method for producing tantalum powder for capacitors. The tantalum powder for capacitors produced by the method has a specific capacitance equivalent to or higher than that of the same grade tantalum powder for capacitors produced by the prior art under high-voltage energizing conditions, a breakdown voltage equivalent to or higher, and can significantly improve the withstand voltage performance of the tantalum powder for capacitors. More importantly and more preferably, while satisfying these favorable properties at the same time, the yield of the tantalum powder can also be improved and the production cost of the tantalum powder can be reduced.
[0008] The present invention relates to a method for producing tantalum powder, comprising the following steps:
[0009] (1) uniformly mixing a tantalum powder raw material, an excess of metallic magnesium and at least one halide selected from an alkali metal and / or an alkaline earth metal, placing the mixture into a sealed reaction container, evacuating the air in the container, and placing the container in a heating furnace;
[0010] (2) raising the temperature of the heating furnace to 700-1000° C. and maintaining the temperature, for example, for 4-20 hours, so that the oxygen in the tantalum powder undergoes a reduction reaction with magnesium in the molten salt and sintering is achieved at the same time;
[0011] (3) After the insulation is completed, the temperature of the heating furnace is set at 600-750° C., the heating furnace is evacuated, for example, to below 10 Pa, for example, to below 5 Pa, and the temperature is maintained under negative pressure, for example, for 3 h to 10 h, so that the excess metal magnesium and the tantalum powder mixture are separated;
[0012] (4) Then, an inert gas is filled into the reaction container to maintain a positive pressure in the reaction container, and then the reaction container is cooled to room temperature and passivated to obtain a mixture containing a halide and tantalum powder;
[0013] (5) separating tantalum powder from the obtained mixture, for example, by washing with water, washing with acid, filtering, or drying.
[0014] Wherein, in step (1), after the air is evacuated, the container is filled with hydrogen-containing gas, for example, by introducing hydrogen-containing gas, or by adding a hydrogen-containing substance and allowing it to release hydrogen. Preferably, the hydrogen-containing substance is separated from other raw materials such as tantalum oxide powder, magnesium metal, alkali metal and / or alkaline earth metal halide, which can be achieved, for example, by placing the hydrogen-containing substance alone in a crucible.
[0015] Preferably, the hydrogen-containing substance is a substance that can release hydrogen at high temperature, such as metal tantalum powder adsorbing hydrogen (also called hydrogen-containing metal tantalum powder or hydrogen-containing tantalum powder), hydrogen-containing niobium powder, hydrogen-containing titanium powder, and hydrogen-containing compounds. In order to simplify the process and improve the purity, hydrogen-containing tantalum powder is preferably used.
[0016] Preferably, the mass ratio of the tantalum powder to the alkali metal and / or alkaline earth metal halide in step (1) is: 1:0.15-10.0, more preferably 1:0.15-3.0. The amount of excess magnesium metal added refers to the amount of magnesium metal that exceeds the theoretical amount of magnesium metal required to completely convert the oxygen in the tantalum powder into magnesium oxide, and the theoretical amount of magnesium metal is calculated based on the reaction equation Ta2O5+5Mg=2Ta+5MgO. The inventors have found that when the amount of magnesium metal used is more than 1.5 times the theoretical amount calculated using the reaction equation, a better effect is achieved. In the present invention, "excess magnesium metal" refers to more than the theoretical amount, preferably more than 1.5 times the theoretical amount, for example more than 3.5 times, preferably 5-12 times, more preferably 7-10 times, and even more preferably 4-7 times.
[0017] Preferably, the magnesium in step (1) is magnesium particles, more preferably 3N5 (i.e., purity of 99.95%) or above magnesium particles, and the lower the metal impurities in the magnesium particles, the better. There is no restriction on the particle size of the magnesium particles. However, after a lot of research, the inventors found that magnesium particles with a particle size of 150-4000 μm are more suitable for this technology. Magnesium particles in this particle size range are not only beneficial to the safety of the storage and transportation process of metallic magnesium, but also conducive to uniform mixing. If the magnesium particles are too fine, the activity is too strong and it is easy to spontaneously ignite; if the magnesium particles are too coarse, it is not conducive to uniform mixing and is not conducive to the optimization of tantalum powder performance.
[0018] Preferably, the alkali metal or alkaline earth metal halide described in step (1) is one or more mixed salts of NaCl, KCl, KF, KI, and / or MgCl2. The alkali metal halide can be sodium chloride and / or potassium chloride. Preferably, it is a mixture of sodium chloride and potassium chloride, more preferably the ratio of sodium chloride to potassium chloride in the mixture is 1:1-10, most preferably about 1:1. The alkali metal or alkaline earth halide is preferably analytically pure, preferably higher purity. The alkali metal and / or alkaline earth metal chloride is preferably in particle form. There is no limitation on its particle size, but the inventors have found that particles of 70 μm-4000 μm are more suitable for the present technology, and the obtained tantalum powder has better pressure resistance.
[0019] Preferably, in step (1), one or more compounds containing B, P, and / or N elements may be added as additives to dope the tantalum powder. In terms of the amount of effective elements, the amount of B element added is preferably 1-100 ppm, more preferably 20-60 ppm; the amount of P element added is preferably 10-200 ppm, more preferably 30-90 ppm; the amount of N element added is preferably 300-2500 ppm, more preferably 500-1200 ppm. It should be understood that although compounds are added here, the effective elements are B, P, and / or N, so the amounts mentioned here are calculated based on the amounts of B, P, and / or N.
[0020] The hydrogen-containing gas described in step (1) is pure hydrogen or a mixed gas of hydrogen and an inert gas. The hydrogen can be gaseous hydrogen or other hydrogen-containing substances that release hydrogen; preferably, the gas pressure in the reaction vessel is a positive pressure. The hydrogen partial pressure in the container is preferably more than 0.050KPa, preferably 0.1-200KPa, more preferably 0.3-50KPa, more preferably 70-100KPa, more preferably 1-20KPa, more preferably 2-10KPa or 10-15KPa, more preferably 0.1-1.0KPa. Too low hydrogen partial pressure cannot promote the sintering effect well, so the hydrogen partial pressure is preferably not too low; conversely, after the hydrogen partial pressure is increased to a certain extent, the ability to improve the effect is weakened, and from the perspective of ensuring the absolute safety of hydrogen use, it is preferably avoided to select too high a hydrogen partial pressure.
[0021] Inert gas generally refers to rare gases, such as helium, neon, and argon. Although nitrogen is sometimes regarded as an inert gas due to its stable properties, in the art, since the temperature of step 2) is relatively high and nitrogen is very active at this high temperature, it is generally considered not to be suitable as an inert protective gas. However, after extensive research, the inventor unexpectedly discovered that a small amount of nitrogen in the above-mentioned inert gas does not damage the inert protective atmosphere and can also achieve nitrogen doping of tantalum powder. From the perspective of achieving a better nitrogen doping effect of tantalum powder, in step (1), when a mixed gas of inert gas and hydrogen-containing gas (such as pure hydrogen) is introduced, it can preferably contain 0.5-10% nitrogen, based on the total amount of hydrogen-containing gas and inert gas.
[0022] Preferably, in step (2), the heating furnace is heated to 750-1000° C., more preferably to 850-1000° C., and the temperature is kept at this temperature for 4-20 hours, preferably 10-20 hours.
[0023] Preferably, in step (3), the temperature of the heating furnace is set to 600-750°C. More preferably, it is set to 620-660°C. Preferably, in this step, the heating furnace is evacuated to 5 Pa, more preferably below 0.5 Pa. There is no restriction on the length of the holding time, as long as the holding time is sufficient to fully separate the excess magnesium metal from the tantalum powder mixture. It should be understood that if the total amount of the mixed material increases, the holding time will be extended accordingly.
[0024] The hydrogen-containing gas in step (1) may be a mixture of hydrogen and an inert gas, and the inert gas in step (1) and step (4) may be the same or different. Preferably, in step (1) and / or (4), a positive pressure is maintained in the reactor.
[0025] Preferably, the method of the present invention further comprises subsequent treatments such as high temperature and high vacuum heat treatment, deoxidation, pickling, etc. after step (5) to obtain tantalum powder suitable for making high-reliability tantalum capacitors. These treatments are all known processes in the prior art. In other words, these treatments can adopt any process known in the prior art. For example, the high temperature and high vacuum heat treatment and passivation here can adopt the methods provided by patents CN201110039272.9, CN201120077798.1, CN201120077680.9, CN201120077305.4, etc., deoxidation can adopt the methods provided by patents CN201420777210.7, CN201420777210.7, pickling can adopt the methods provided by patents CN201210548101.3, CN201280077499.5, CN201210548008.2, etc.
[0026] As an alternative to doping N, P and / or B elements in step (1), the present invention may also include a separate step of doping these elements, for example, after step (5). Of course, raw materials containing these elements may also be used directly. These elements may also be added in the aforementioned high temperature and high vacuum heat treatment step. It is particularly preferred to add the P element. Adding the P element can increase the specific volume. As long as the total amount of P doping is controlled, the effect of increasing the specific volume is the same regardless of when it is added.
[0027] The present invention also relates to a tantalum powder suitable for making a high-reliability tantalum capacitor and an anode block obtained from the tantalum powder, characterized in that the anode block made from the tantalum powder has a higher specific capacitance when the electrical performance is tested under high-voltage energizing conditions, and has a higher breakdown voltage in a breakdown voltage test.
[0028] The present invention has no restrictions on the raw material of tantalum powder to be processed, which can be tantalum powder obtained by reducing tantalum oxide with magnesium, tantalum powder obtained by reducing potassium fluorotantalate with sodium, or tantalum powder obtained by other reduction processes, and can be tantalum powder processed into flakes by physical methods, or tantalum powder after metal tantalum is hydrogenated and crushed. Although a certain amount of oxygen is inevitably present in these tantalum powders, the present invention does not have any special requirements for the oxygen content. There is no requirement for the specific surface area of tantalum powder. However, the inventors have found that the tantalum powder obtained by reducing tantalum oxide with magnesium is better.
[0029] Moreover, the process of the present invention is simple and easy to control. For example, in all steps of the present invention, microwaves are not used and excessively high temperatures are not used. Therefore, the equipment used is also relatively simple, and the tantalum powder sintering process is safer.
[0030] Although hydrogen cannot reduce tantalum oxide, it plays an important role in the present invention. Without being bound by general theories, combined with the theoretical analysis principle of powder liquid phase sintering, the inventor believes that the reasons for the excellent effect of the present invention are as follows: in step (2), as the temperature rises, the metal magnesium and the alkali metal or alkaline earth metal chloride melt and present a liquid phase. In the presence of hydrogen-containing gas in the atmosphere, the hydrogen-containing gas promotes the diffusion of oxygen content on the surface of the tantalum powder to the liquid magnesium, making reduction easier to occur and increasing the surface activity of the tantalum powder particles; in the molten metal magnesium and alkali metal or alkaline earth metal chloride, the edges and corners of the large particles in the tantalum powder, the micro-convexities and ultra-fine tantalum powder particles are dissolved in the liquid phase. As the process continues, when the concentration of tantalum in the liquid phase exceeds the saturation concentration, it will preferentially deposit in certain parts of the large tantalum particles and merge into a part of the large particles. At the same time, in the presence of hydrogen, it can promote further sintering between the tantalum powder particles, so that the particles are smooth, the sintering neck is thick, and the ultra-fine particles are few. Due to the low sintering temperature of this process relative to the melting point of tantalum metal at around 3000°C, tantalum powder can be sintered into a microstructure suitable for making tantalum electrolytic capacitors. At the same time, the effective surface area of tantalum powder for capacitors is reduced less, which is conducive to maintaining the specific volume of tantalum powder for capacitors. After that, the obtained tantalum powder is subjected to high-temperature and high-vacuum sintering, oxygen reduction, and acid washing according to the existing technology, and accordingly, tantalum powder suitable for preparing high-voltage and high-reliability capacitors will be obtained.
[0031] If the tantalum powder as a product of the process according to the invention is sintered to form anode blocks, they have an improved microstructure, in particular the absence of ultrafine pores in the resulting anode blocks. These ultrafine pores are detrimental to the electrical properties, in particular leakage current and ESR (equivalent series resistance). BRIEF DESCRIPTION OF THE DRAWINGS
[0032] The following drawings are provided for a better understanding of the present invention. These drawings are exemplary and are not intended to limit the scope of the present invention.
[0033] Figure 1The scanning electron microscope picture of the tantalum powder obtained according to the present invention is given.
[0034] The accompanying figure illustrates that the obtained tantalum powder has a more uniform distribution, smooth particles, thick sintering necks, and fewer ultrafine particles. DETAILED DESCRIPTION
[0035] In order to further illustrate the present invention, the preferred embodiments of the present invention are described below in conjunction with the examples, and it can be clearly seen that the objects, features and advantages of the present invention. However, these descriptions are only for further illustrating the features and advantages of the present invention, rather than for limiting the present invention. If the specific conditions are not specified in the examples, they are carried out under normal conditions. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be obtained commercially.
[0036] For the purpose of this specification, all numbers indicating the amount of ingredients, reaction conditions, etc. in the specification and claims should be understood as being modified by the term "about" in all cases, unless otherwise specified. Accordingly, the numerical parameters given in the following specification and the appended claims are approximate values, which may vary according to the desired properties that the present invention attempts to obtain, unless otherwise indicated. At least, and without intending to limit the application of the doctrine of equivalents to the scope of the claims, each numerical parameter should be interpreted at least in accordance with the number of reported significant figures and in accordance with conventional rounding techniques.
[0037] The analysis of impurity content in tantalum powder is carried out in accordance with the Chinese standard GB / T15076.1~15076.15, and the physical properties are carried out in accordance with the provisions of the industry standard YS / T573-2015. The test of electrical properties in tantalum powder is carried out in accordance with the provisions of the Chinese standard GB / T3137.
[0038] Example 1
[0039] Take 5.0kg of magnesium to reduce tantalum oxide to obtain tantalum powder, add 2.6% (4.95 times the theoretical amount) of metal magnesium particles based on the weight of tantalum powder, and add 3.75kg of potassium chloride (KCl), mix well and put into a closed reaction container, and evacuate the air in the reaction container. Pass a mixed gas of hydrogen and argon into the reaction container, control the hydrogen partial pressure to 20KPa, and keep the reaction container under positive pressure. Put the reaction container into a heating furnace and heat it to 930℃, keep it warm for 15.0 hours, then reduce the temperature to 640℃ to evacuate, reduce the pressure in the reaction container to 5.7Pa, keep it warm for 5 hours, and stop evacuating. Then pass argon into the reaction container to maintain positive pressure, cool it to room temperature, and perform passivation treatment; wash the obtained halide and tantalum powder mixture with water, pickle, filter, and dry it to obtain 4.63kg of tantalum powder, calculate the tantalum powder yield, analyze the tantalum powder Fsss particle size, and the results are listed in Table 1.
[0040] The obtained tantalum powder was added with 50ppm phosphorus and heated at 1400℃ and pressure less than 5.0×10 -3 Pa, high temperature and high vacuum heat treatment for 0.5 hours, and then deoxidation and pickling are carried out to obtain tantalum powder. The tantalum powder is made into anode blocks according to the anode block mass, pressing density, anode block sintering temperature, and sintering time specified in Table 2, and other conditions are made according to the requirements of the aforementioned GB / T3137, and energized under 200V conditions, and then the electrical properties are tested according to the requirements of the aforementioned GB / T3137. The measured results are listed in Table 2. In the specific capacitance test, after the test with 30% H2SO4 solution, the test was carried out with 10% H3PO4 solution, and the measured results are listed in Table 1.
[0041] Comparative Example 1
[0042] Take 5.0kg of magnesium to reduce tantalum oxide to obtain tantalum powder, add 2.6% (4.95 times the theoretical amount) of metal magnesium particles based on the weight of tantalum powder, and add 3.75kg of potassium chloride (KCl), mix well and put into a reaction container, and evacuate the air in the reaction container. Pass argon gas into the reaction container, keep the reaction container under positive pressure, put the reaction container into a heating furnace and heat it, raise the temperature to 930℃, keep it warm for 15.0 hours, then reduce the temperature to 640℃ to evacuate, reduce the pressure in the reaction container to 5.7Pa, keep it warm for 5 hours, and stop evacuating. Pass argon gas into the reaction container again to maintain positive pressure, cool it to room temperature, and perform passivation treatment; wash the obtained halide and tantalum powder mixture with water, pickle, filter, and dry it to obtain 4.12kg of tantalum powder, calculate the tantalum powder yield, analyze the tantalum powder Fsss particle size, and the results are listed in Table 1.
[0043] The obtained tantalum powder was added with 50ppm phosphorus and heated at 1400℃ and pressure less than 5.0×10 -3 Pa, high temperature and high vacuum heat treatment for 0.5 hours, and then deoxidation and pickling are carried out to obtain tantalum powder. The tantalum powder is made into anode blocks according to the anode block mass, pressing density, anode block sintering temperature, and sintering time specified in Table 2, and other conditions are made according to the requirements of the aforementioned GB / T3137, and energized under 200V conditions, and then the electrical properties are tested according to the requirements of the aforementioned GB / T3137. The measured results are listed in Table 2. In the specific capacitance test, after the test with 30% H2SO4 solution, the test was carried out with 10% H3PO4 solution, and the measured results are listed in Table 1.
[0044] Example 2
[0045] Take 5.0kg of magnesium to reduce tantalum oxide to obtain tantalum powder, add 3.3% (6.98 times the theoretical amount) of metal magnesium particles based on the weight of tantalum powder, and add 1.0kg of potassium chloride (KCl) and 1.0kg of sodium chloride (NaCl), mix well and put into a reaction container, and evacuate the air in the reaction container. Pass a mixed gas of hydrogen and argon into the reaction container, control the hydrogen partial pressure to 0.350KPa, and keep the reaction container under positive pressure. Put the reaction container in a heating furnace and heat it to 970℃, keep it warm for 20.0 hours, then reduce the temperature to 680℃ to evacuate, reduce the pressure in the reaction container to 5.7Pa, keep it warm for 8 hours, and stop evacuating. Then, argon gas was introduced into the reaction container to maintain positive pressure, and the temperature was lowered to room temperature for passivation treatment. The obtained halide and tantalum powder mixture was washed with water, acid-washed, filtered, and dried to obtain 4.70 kg of tantalum powder. The tantalum powder yield was calculated, and the particle size of the tantalum powder Fsss was analyzed. The results are listed in Table 1.
[0046] The obtained tantalum powder was heated at 1450°C and a pressure lower than 5.0×10 -3 Pa, high temperature and high vacuum heat treatment for 0.5 hours, and then deoxidation and acid washing to obtain tantalum powder. The tantalum powder is made into anode blocks according to the anode block mass, pressing density, anode block sintering temperature, and sintering time specified in Table 2, and other conditions are in accordance with the aforementioned GB / T3137 requirements, energized under 300V conditions, and then the electrical properties are tested according to the aforementioned GB / T3137 requirements. The measured results are listed in Table 2. In the specific capacitance test, after the test with 30% H2SO4 solution, the test was conducted with 10% H3PO4 solution, and the measured results are listed in Table 1.
[0047] Comparative Example 2
[0048] Take 5.0kg of magnesium to reduce tantalum oxide to obtain tantalum powder, add 3.3% (6.98 times the theoretical amount) of metal magnesium particles based on the weight of tantalum powder, and add 1.0kg of potassium chloride (KCl) and 1.0kg of sodium chloride (NaCl) at the same time, mix well and put into a reaction container, and evacuate the air in the reaction container. Pass argon gas into the reaction container, keep the reaction container under positive pressure, put the reaction container into a heating furnace and heat it, raise the temperature to 970℃, keep it warm for 20.0 hours, then reduce the temperature to 680℃ to evacuate, reduce the pressure in the reaction container to 5.7Pa, keep it warm for 8 hours, and stop evacuating. Pass argon gas into the reaction container again, keep it under positive pressure, cool it to room temperature, and perform passivation treatment; wash the obtained halide and tantalum powder mixture with water, pickle it, filter it, and dry it to obtain 4.04kg of tantalum powder, calculate the tantalum powder yield, analyze the tantalum powder Fsss particle size, and the results are listed in Table 1.
[0049] The obtained tantalum powder was heated at 1450°C and a pressure lower than 5.0×10-3 Pa, high temperature and high vacuum heat treatment for 0.5 hours, and then deoxidation and acid washing to obtain tantalum powder. The tantalum powder is made into anode blocks according to the anode block mass, pressing density, anode block sintering temperature, and sintering time specified in Table 2, and other conditions are in accordance with the aforementioned GB / T3137 requirements, energized under 300V conditions, and then the electrical properties are tested according to the aforementioned GB / T3137 requirements. The measured results are listed in Table 2. In the specific capacitance test, after the test with 30% H2SO4 solution, the test was conducted with 10% H3PO4 solution, and the measured results are listed in Table 1.
[0050] Example 3
[0051] Take 5.0kg of magnesium to reduce tantalum oxide to obtain tantalum powder, add 7.3% (7.91 times the theoretical amount) of metal magnesium particles based on the weight of tantalum powder, and add 2.0kg of potassium chloride (KCl) and 2.0kg of sodium chloride (NaCl), mix well and put into a reaction container, and evacuate the air in the reaction container. Pass a mixed gas of hydrogen and argon into the reaction container, control the hydrogen partial pressure to 50KPa, and keep the reaction container under positive pressure. Put the reaction container in a heating furnace and heat it to 830℃, keep it warm for 12.0 hours, then reduce the temperature to 650℃ to evacuate, reduce the pressure in the reaction container to 5.7Pa, keep it warm for 8 hours, and stop evacuating. Then, argon gas was introduced into the reaction container to maintain positive pressure, and the temperature was lowered to room temperature for passivation treatment. The obtained halide and tantalum powder mixture was washed with water, acid-washed, filtered, and dried to obtain 4.50 kg of tantalum powder. The tantalum powder yield was calculated, and the particle size of the tantalum powder Fsss was analyzed. The results are listed in Table 1.
[0052] The obtained tantalum powder was heated at 1250°C and a pressure lower than 5.0×10 -3 Pa for 0.5 hours under high temperature and high vacuum heat treatment, and then deoxidation and pickling to obtain tantalum powder. The tantalum powder is made into anode blocks according to the anode block mass, pressing density, anode block sintering temperature, and sintering time specified in Table 1, and other conditions are made according to the aforementioned GB / T3137 requirements, and energized under 60V conditions, and then the electrical properties are tested according to the aforementioned GB / T3137 requirements. The measured results are listed in Table 2. In the specific capacitance test, after the test with 30% H2SO4 solution, the test was conducted with 10% H3PO4 solution, and the measured results are listed in Table 1.
[0053] Comparative Example 3
[0054] Take 5.0kg of magnesium to reduce tantalum oxide to obtain tantalum powder, add 7.3% (7.91 times the theoretical amount) of metal magnesium particles based on the weight of tantalum powder, add 2.0kg of potassium chloride (KCl) and 2.0kg of sodium chloride (NaCl), add 50ppm of phosphorus, mix well and put into a reaction container, and evacuate the air in the reaction container. Enter argon gas into the reaction container, keep the reaction container under positive pressure, put the reaction container into a heating furnace and heat it, raise the temperature to 830℃, keep it warm for 12.0 hours, then reduce the temperature to 650℃ to evacuate, reduce the pressure in the reaction container to 5.7Pa, keep it warm for 8 hours, and stop evacuating. Enter argon gas into the reaction container again, keep the positive pressure, then cool it to room temperature and perform passivation treatment; wash the obtained halide and tantalum powder mixture with water, pickle it, filter it, and dry it to obtain 3.81kg of tantalum powder, calculate the tantalum powder yield, analyze the tantalum powder Fsss particle size, and the results are listed in Table 1.
[0055] The obtained tantalum powder was heated at 1250°C and a pressure lower than 5.0×10 -3 Pa for 0.5 hours under high temperature and high vacuum heat treatment, and then deoxidation and pickling to obtain tantalum powder. The tantalum powder is made into anode blocks according to the anode block mass, pressing density, anode block sintering temperature, and sintering time specified in Table 2, and other conditions are made according to the requirements of GB / T3137, and energized under 60V conditions, and then the electrical properties are tested according to the requirements of GB / T3137, and the measured results are listed in Table 2. In the specific capacitance test, after the test with 30% H2SO4 solution, the test was conducted with 10% H3PO4 solution, and the measured results are listed in Table 1.
[0056] Table 1 Molten salt assisted sintering yield and Fsss particle size test results
[0057]
[0058] Table 2 Electrical properties of finished tantalum powder
[0059]
[0060] Example 4
[0061] Take 5.0kg of sodium to reduce potassium fluorotantalate to obtain tantalum powder, add 5.0% (4.09 times the theoretical amount) of magnesium particles based on the weight of tantalum powder, 2.0kg of potassium chloride (KCl) and 2.0kg of sodium chloride (NaCl), mix well and put into a reaction container, then put 800g of tantalum metal containing 5237ppm of hydrogen in a crucible separately, and put it into a unified reaction container separately from the tantalum powder, and separate the air in the reaction container. Pass argon into the reaction container, put the reaction container into a heating furnace and heat it. During the heating process, the hydrogen-containing tantalum metal releases hydrogen, heat to 880℃, then keep it warm for 10.0 hours, then reduce the temperature to 640℃ to evacuate, reduce the pressure in the reaction container to 5.7Pa, keep it warm for 10 hours, and stop evacuating. After the insulation was completed, argon gas was introduced into the reaction container to maintain positive pressure, and the temperature was lowered to room temperature for passivation treatment; the metallic tantalum that provided hydrogen was recovered separately, and the obtained halide and tantalum powder mixture was washed with water, acid-washed, filtered, and dried to obtain 4.50 kg of tantalum powder, the tantalum powder yield was calculated, and the tantalum powder Fsss particle size was analyzed. The results are listed in Table 3.
[0062] The obtained tantalum powder was added with 90ppm phosphorus and heated at 1240℃ and pressure less than 5.0×10 -3 Pa for 0.5 hours under high temperature and high vacuum heat treatment, and then deoxidation and pickling are performed to obtain tantalum powder. According to the anode block mass, pressing density, anode block sintering temperature, and sintering time specified in Table 4, the other conditions are in accordance with the aforementioned GB / T3137 requirements. The obtained tantalum powder is made into an anode block, energized under 60V conditions, and then the electrical properties are tested in accordance with the aforementioned GB / T3137 requirements. The measured results are listed in Table 4. In the specific capacitance test, after the test with 30% H2SO4 solution, the test was conducted with 10% H3PO4 solution, and the measured results are listed in Table 1.
[0063] Comparative Example 4
[0064] Take 5.0kg of sodium containing 800ppm nitrogen compound to reduce potassium fluorotantalate to obtain tantalum powder, add 5.0% (4.09 times the theoretical amount) of metal magnesium particles based on the weight of tantalum powder, and 2.0kg of potassium chloride (KCl) and 2.0kg of sodium chloride (NaCl), mix well and put into a reaction container, separate the air in the reaction container. Pass argon into the reaction container, put the reaction container into a heating furnace and heat it to 880℃, keep it warm for 10.0 hours, then reduce the temperature to 640℃ to evacuate, reduce the pressure in the reaction container to 5.7Pa, keep it warm for 10 hours, and stop evacuating. After the insulation is completed, pass argon into the reaction container again to maintain positive pressure, cool it to room temperature, and perform passivation treatment; wash the obtained halide and tantalum powder mixture with water, pickle, filter, and dry it to obtain 4.25kg of tantalum powder, calculate the tantalum powder yield, analyze the tantalum powder Fsss particle size, and the results are listed in Table 3.
[0065] The obtained tantalum powder was added with 90ppm phosphorus and heated at 1240℃ and pressure less than 5.0×10 -3 Pa for 0.5 hours under high temperature and high vacuum heat treatment, and then deoxidation and pickling are performed to obtain tantalum powder. According to the anode block mass, pressing density, anode block sintering temperature, and sintering time specified in Table 4, the other conditions are in accordance with the aforementioned GB / T3137 requirements. The obtained tantalum powder is made into an anode block, energized under 60V conditions, and then the electrical properties are tested in accordance with the aforementioned GB / T3137 requirements. The measured results are listed in Table 4. In the specific capacitance test, after the test with 30% H2SO4 solution, the test was conducted with 10% H3PO4 solution, and the measured results are listed in Table 1.
[0066] Example 5
[0067] Take 5.0kg of flaky tantalum powder containing 50ppm of boron compound, add 5.0% (6.12 times of theoretical amount) of magnesium particles based on the weight of tantalum powder, 2.0kg of potassium chloride (KCl) and 2.0kg of sodium chloride (NaCl), mix well and put into a reaction container, then put 800g of tantalum metal containing 5237ppm of hydrogen in a crucible separately, put it into a unified reaction container separately from tantalum powder, separate the air in the reaction container. Pass argon into the reaction container, put the reaction container into a heating furnace and heat it, the hydrogen-containing tantalum metal releases hydrogen during the heating process, heat to 920℃, keep warm for 10.0 hours, then reduce the temperature to 660℃ to evacuate, reduce the pressure in the reaction container to 5.7Pa, keep warm for 10 hours, and stop evacuating. After the insulation was completed, argon gas was introduced into the reaction container to maintain positive pressure, and the temperature was lowered to room temperature for passivation treatment; the metallic tantalum that provided hydrogen was recovered separately, and the obtained halide and tantalum powder mixture was washed with water, acid-washed, filtered, and dried to obtain 4.70 kg of tantalum powder, the tantalum powder yield was calculated, and the tantalum powder Fsss particle size was analyzed. The results are listed in Table 3.
[0068] The obtained tantalum powder was added with 30ppm phosphorus and heated at 1360℃ and pressure less than 5.0×10 -3 Pa for 0.5 hours under high temperature and high vacuum heat treatment, and then deoxidation and pickling are performed to obtain tantalum powder. According to the anode block mass, pressing density, anode block sintering temperature, and sintering time specified in Table 4, the other conditions are in accordance with the aforementioned GB / T3137 requirements. The obtained tantalum powder is made into an anode block, energized under 150V conditions, and then the electrical properties are tested according to the aforementioned GB / T3137 requirements. The measured results are listed in Table 4. In the specific capacitance test, after the test with 30% H2SO4 solution, the test was conducted with 10% H3PO4 solution, and the measured results are listed in Table 1.
[0069] Comparative Example 5
[0070] Take 5.0kg of flaky tantalum powder containing 50ppm of boron, add 5.0% (6.12 times the theoretical amount) of magnesium particles based on the weight of tantalum powder, 2.0kg of potassium chloride (KCl) and 2.0kg of sodium chloride (NaCl), mix well and put into a reaction container, separate the air in the reaction container. Pass argon into the reaction container, put the reaction container into a heating furnace and heat it to 920℃, keep it warm for 10.0 hours, then reduce the temperature to 660℃ to evacuate, reduce the pressure in the reaction container to 5.7Pa, keep it warm for 10 hours, and stop evacuating. After the insulation is completed, pass argon into the reaction container again to maintain positive pressure, cool it to room temperature, and perform passivation treatment; wash the obtained halide and tantalum powder mixture with water, pickle, filter, and dry it to obtain 4.00kg of tantalum powder with improved particle structure, calculate the tantalum powder yield, analyze the tantalum powder Fsss particle size, and list the results in Table 3.
[0071] The obtained tantalum powder was added with 30ppm phosphorus and heated at 1360℃ and pressure less than 5.0×10 -3 Pa for 0.5 hours under high temperature and high vacuum heat treatment, and then deoxidation and pickling are performed to obtain tantalum powder. According to the anode block mass, pressing density, anode block sintering temperature, and sintering time specified in Table 4, the other conditions are in accordance with the aforementioned GB / T3137 requirements. The obtained tantalum powder is made into an anode block, energized under 150V conditions, and then the electrical properties are tested according to the aforementioned GB / T3137 requirements. The measured results are listed in Table 4. In the specific capacitance test, after the test with 30% H2SO4 solution, the test was conducted with 10% H3PO4 solution, and the measured results are listed in Table 1.
[0072] Table 3 Molten salt assisted sintering yield and Fsss particle size test results
[0073]
[0074]
[0075] Table 4 Electrical properties of finished tantalum powder
[0076]
[0077] It can be seen from Table 1 and Table 3 that, compared with the prior art, the present invention has the following advantages:
[0078] The tantalum powder produced by the method of the present invention has a significantly higher yield of tantalum powder in the molten salt assisted heat treatment process, which undoubtedly saves production costs. Therefore, the tantalum powder for producing high-reliability tantalum capacitors of the present invention has a lower cost advantage.
[0079] Moreover, the particle size of tantalum powder Fsss is relatively large, which is beneficial to improving the reliability of tantalum capacitors.
[0080] It can also be seen from Table 2 and Table 4 that the tantalum powder manufactured by the present invention is energized under high-voltage conditions and the electrical properties of the energized block are tested. Compared with the prior art, it is found that its electrical properties are comparable or even better. Moreover, it can also be seen that the anode block made of the tantalum powder described in the present invention has a smaller difference in specific capacitance obtained by testing with different acid solutions after energization. It is generally believed that phosphoric acid and sulfuric acid have different surface tensions and different abilities to penetrate into the ultrafine pores in the anode block. Therefore, the difference in specific capacitance reflects the presence of ultrafine pores in the anode block, that is, the greater the difference, the more ultrafine pores. Therefore, these two tables also prove that the use of the tantalum powder according to the present invention can obtain an anode block with fewer ultrafine pores and a better microstructure.
[0081] It can also be seen from Tables 1 and 2 that in the present invention, when the preparation methods of the raw material tantalum powder are the same, tantalum powder with a relatively large surface area and a relatively high oxygen content is used as the raw material, and finally a tantalum powder with a higher specific volume can be obtained.
Claims
1. A method for producing tantalum powder, characterized in that: The method comprises a sintering process carried out in a hydrogen-containing atmosphere, preferably the hydrogen-containing atmosphere is pure hydrogen or a mixture of hydrogen and an inert gas; and / or The hydrogen-containing gas is obtained by introducing a gaseous hydrogen-containing gas, or by adding a hydrogen-containing substance and releasing hydrogen.
2. A method for producing tantalum powder, comprising the following steps: (1) uniformly mixing a tantalum powder raw material (e.g., tantalum powder obtained by reducing tantalum oxide with magnesium, tantalum powder obtained by reducing potassium fluorotantalate with sodium, tantalum powder processed into flakes by physical methods, or tantalum powder crushed by hydrogenation of metal tantalum) with metal magnesium (e.g., magnesium particles) and at least one halide selected from alkali metals and / or alkaline earth metals, placing the mixture into a sealed reaction container, evacuating the air in the container, and placing the container in a heating furnace; (2) raising the temperature of the heating furnace to 700-1000° C. (preferably 750-950° C., more preferably 800-900° C.) and maintaining the temperature, for example, for 4 h to 20 h (preferably 10 h to 20 h), so that the oxygen in the raw material tantalum powder undergoes a reduction reaction with magnesium in the molten salt and sintering is achieved; (3) After the insulation is completed, the temperature is lowered to 600-750° C. (preferably to 620-680° C.), the heating furnace is evacuated, for example, to a pressure below 10 Pa (preferably below 5 Pa, more preferably below 0.5 Pa), and the temperature is maintained under negative pressure to fully separate the excess magnesium metal and the tantalum powder mixture; (4) introducing an inert gas such as argon into the reaction vessel (preferably maintaining the reaction vessel at a positive pressure), followed by cooling to room temperature and performing a passivation treatment to obtain a mixed material containing a halide and tantalum powder; (5) For example, the obtained mixed material is subjected to water washing, acid washing, filtering and drying to separate the tantalum powder, and optionally the following steps: (6) High temperature and high vacuum heat treatment; (7) Separation, for example, by acid washing, filtering, or drying. in, In step (1), after the air is evacuated, the container is filled with a hydrogen-containing gas, for example, by introducing a hydrogen-containing gas, or by adding a hydrogen-containing substance (for example, metal tantalum absorbing hydrogen) and allowing it to release hydrogen.
3. The production method according to claim 2, characterized in that: The mass ratio of the tantalum powder to the alkali metal and / or alkaline earth metal halide in step (1) is 1:0.15-10.0, more preferably 1:0.15-3.0, more preferably 1:1.5-2.
5.
4. The production method according to claim 2 or 3, characterized in that: The amount of excess metallic magnesium added in step (1) is 1.5 times or more of the theoretical amount of metallic magnesium required to convert oxygen in the tantalum powder into magnesium oxide, preferably 3.5 times or more of the theoretical amount, preferably 5-12 times, more preferably 7-10 times, and even more preferably 4-7 times.
5. The production method according to any one of claims 2 to 4, characterized in that: The alkali metal or alkaline earth metal halide in step (1) is a mixture of one or more of NaCl, KCl, KF, KI, MgCl2, preferably a mixture of NaCl and KCl, more preferably a mass ratio of NaCl to KCl in the mixture is 1:1-10, most preferably about 1:
2.
6. The production method according to any one of claims 2 to 5, characterized in that: In step (1), one or more compounds containing B, P, and / or N elements are added as additives to dope the tantalum powder. Preferably, Calculated on the basis of the amount of effective elements, the amount of B element added is 1-100 ppm, more preferably 20-60 ppm; and / or the added P element is 10-200ppm, more preferably 30-90ppm; And / or the added N element is 300-2500ppm, more preferably 500-1200ppm.
7. The production method according to claim 2-6, characterized in that: The hydrogen partial pressure in step (2) exceeds 0.050 KPa, preferably 0.1-200 KPa, more preferably 0.3-50 KPa, more preferably 50-100 KPa, more preferably 1.0-20 KPa, more preferably 2.0-10 KPa or 10-15 KPa, more preferably 0.1-1.0 KPa.
8. The production method according to any one of claims 2 to 7, characterized in that: The inert gas in step (2) is the same as or different from the inert gas in step (4), and / or preferably, the inert gas in step (2) and the inert gas in step (4) are at a positive pressure in the container.
9. Tantalum powder produced by the production method according to any one of claims 1 to 8.
10. Use of tantalum powder according to claim 9 in capacitors.
Citation Information
Patent Citations
Thermal treatment method of tantalum powder
CN102120258A
Stirring water-washing method and device for producing tantalum powder by reducing potassium fluotantalate via metallic sodium
CN102990076B
Method for purifying tantalum powder
CN102994780B
Method and apparatus for purifying target powder
CN105051223B
Tantalum metal surface inactivating equipment with argon forced cooling device
CN202072753U